Depression risk in patients with heart failure in primary care practices in Germany. (16th June 2016) - Konrad, Marcel; Bohlken, Jens; Rapp, Michael A; Kostev, Karel
ABSTRACT: Background: The goal of this study was to estimate the prevalence of and risk factors for diagnosed depression in heart failure (HF) patients in German primary care practices. Methods: This study was a retrospective database analysis in Germany utilizing the Disease Analyzer® Database (IMS Health, Germany). The study population included 132, 994 patients between 40 and 90 years of age from 1, 072 primary care practices. The observation period was between 2004 and 2013. Follow-up lasted up to five years and ended in April 2015. A total of 66, 497 HF patients were selected after applying exclusion criteria. The same number of 66, 497 controls were chosen and were matched (1:1) to HF patients on the basis of age, sex, health insurance, depression diagnosis in the past, and follow-up duration after index date. Results: HF was a strong risk factor for diagnosed depression ( p < 0.0001). A total of 10.5% of HF patients and 6.3% of matched controls developed depression after one year of follow-up ( p < 0.001). Depression was documented in 28.9% of the HF group and 18.2% of the control group after the five-year follow-up ( p < 0.001). Cancer, dementia, osteoporosis, stroke, and osteoarthritis were associated with a higher risk of developing depression. Male gender and private health insurance were associated with lower risk of depression. Conclusions: The risk of diagnosed depression is significantly increased in patients with HF compared to patients without HF in primary care practices in Germany.